Correlation of only children's perceived parental nurturance to their self-esteem - Borja, Trina Mari Z. (College of Home Economics, University of the Philippines Diliman, 2019)
This study seeks to explore the relationship of parental nurturance and self-esteem of only children who are currently living in Quezon City. A total of 50 only child participants answered two quantitative instruments such as the Self-Esteem Rating Scale (SERS) and Parental Nurturance Scale (PNS). Participants were gathered by the use of snowball sampling technique as well as network-based sampling in social media applications. Spearman Rank-Order Correlation and statistical tools such as mean, median and mode were used to describe the data. Aside from this, a 3-item survey questionnaire was also answered by 10 participants to supplement the quantitative data. Four themes of definitions of self-esteem were revealed in the survey questionnaire. These include confidence in abilities, measurement of value, attitude towards life and product of one's experiences. Meanwhile, factors that contribute to the increase or decrease of self-esteem were identified based on performance, social support, tangible things and consciousness. Characteristics of nurturing parents were also identified as loving, disciplining, providing and respecting individuals. Consistency in past literature as the assumption of only children having high level of self-esteem is proven using the SERS. . Similarly, results for PNS also yielded high Spearman Rank-Order Coefficients in terms of parental and maternal nurturance. As a result, a very strong positive correlation was identified when these coefficients were compared to the critical value of the research. Findings of the study will contribute to studies on the family dynamics of single-child families.